Integrated pest management approaches against major insect pests and diseases of tomato - K V, Raghavendra; Balodi, Rekha; Chander, Subhash (Indian Horticulture, 2023)
Tomato is one of the most important vegetable crops of India, grown in 789.20 thousand ha area with 25.00 mt/ha productivity. Pests and diseases are biotic constraints to tomato production. In recent past, due to climate variabilitycoupled with changes in the cropping pattern, there has been a paradigm shift in infestation of pests in time and space, causing huge losses. According to base line survey conducted by ICAR–NCIPM, New Delhi, farmers spray 25-30 rounds of cocktail chemical pesticides in a season, leading to various adverse effects. The only alternative to overcome the problems due to sole dependence on pesticides is to adopt Integrated Pest Management (IPM) practices as explained in this article. besides guiding the farmers to reduce the over-reliance upon chemical pesticides, this will help them to grow tomatoes according to Good Agriculture Practices (GAP) standards.